Performance of Xpert® MTB/RIF in detecting Multidrug-Resistance Tuberculosis in West Java, Indonesia - Edhyana Sahiratmadja; Gde Sindu Mega; Basti Andriyoko; Ida Parwati (Majalah Kedokteran Bandung, 2020)
Indonesia is the 2nd country with the highest tuberculosis (TB) caseload in the world. Inappropriate TB treatment may lead to multidrug-resistance tuberculosis (MDR-TB) development. TB rapid detection is important, and very much needed, to prevent transmission and deaths due to this disease. The Xpert® MTB/RIF is proposed to address this problem. This study aimed to assess the performance of the Xpert® MTB/RIF test in West Java, Indonesia. This was a cross-sectional study conducted on MDR-TB suspects referred to Dr. Hasan Sadikin General Hospital Bandung, West Java, Indonesia, using data from the eTB Manager. The performance of Xpert® MTB/RIF testing and its validity was tested against conventional drug susceptibility testing (DST). In total, data from 4,452 MDR-TB suspects were retrieved but only 578 data that had both DST and Xpert® MTB/RIF results were included in the study. The Xpert® MTB/RIF showed a sensitivity of 88% (95%CI: 85%-91%), specificity of 66% (95%CI: 60%-72%), positive predictive value of 79% (95%CI: 75%-83%), and negative predictive value of 80% (95%CI: 74%-85%), with a detection accuracy of 79%. Xpert® MTB/RIF test in this study shows a good performance for the diagnosis of MDR-TB when compared to the Mycobacterium tuberculosis culture as the gold standard. Therefore, rapid Xpert® MTB/RIF examination is recommended for MDR-TB screening for countries with a high TB burden as a complementary tool to the reference standard test. Performa Xpert® MTB/RIF Dalam Mendeteksi Tuberculosis Resisten Obat di Jawa Barat, IndonesiaIndonesia adalah negara ke-2 dengan jumlah kasus tuberkulosis (TB) tertinggi di dunia. Pengobatan TB yang tidak sesuai dapat mengakibatkan kuman TB menjadi resisten terhadap obat TB yang disebut TB multidrug-resistances (TB-MDR). Untuk itu diperlukan alat deteksi yang mumpuni sehingga kuman TB-DR dapat segera didiagnosis dan diberikan pengobatan yang tepat; dengan demikian pencegahan dan kematian akibat TB dapat ditekan. Penelitian ini bertujuan untuk mengukur performa mesin Xpert® MTB/RIF dalam mendeteksi kuman TB-MDR di Jawa Barat, Indonesia. Studi potong lintang dilakukan dengan mengambil data dari 4452 pasien terduga TB-MDR yang terregistrasi di eTB Manager selama tahun 2012-2016 yang dikirim ke Rumah Sakit Dr. Hasan Sadikin Bandung. Walaupun demikian, hanya 578 yang memiliki hasil test kultur untuk mengetahui sensitivitas obat TB. Dari kedua test tersebut, didapatkan Xpert® MTB/RIF memiliki sensitivitas 88% (95% IK: 85%-91%), spesifisitas 66% (95%CI: 60%-72%), positive predictive value 79% (95% IK: 75%-83%), dan negative predictive value 80% (95% IK: 74%-85%), dengan akurasi 79%. Test TB-MDR menggunakan Xpert® MTB/RIF pada penelitian ini menunjukkan performa yang baik, sehingga test ini sangat direkomendasikan untuk deteksi TB-MDR yang cepat, utamanya di daerah dengan prevalensi TB yang tinggi.